The Effect of Facility and Services Quality on Patient Satisfaction in Noeranny's Maternity Clinic - Adi Suparwo (Institute of Computer Science (IOCS), 2022)
Satisfaction is the most meaningful element for a company engaged in services, because with appropriate satisfaction it will be able to create new customers and retain existing customers. So we need the right steps for the company in order to increase customer satisfaction through the factors that support it. This study aims to determine the effect of facilities and service quality on patient satisfaction at the Noeranny Maternity Clinic. The analytical technique used to analyze the effect of the variables in this study was multiple regression analysis, t test and F test. The population used was patients who visited the Maternity Clinic Noeranny Bandung. The sample obtained is 100 respondents. The results showed that the facilities and service quality, either partially or simultaneously, had an effect on patient satisfaction. Based on the results of the study, the Noeranny Maternity Clinic must always pay attention to the facilities provided by updating the facilities and infrastructure at the clinic, then providing maximum service quality by continuing to provide comfort and safety to patients so that they can give a positive impression on patients.